¿90 días para morir?: La extinción de la medida cautelar concedida judicialmente antes del inicio del arbitraje por falta de constitución del tribunal arbitral - Rojas Ventura de Dominguez, Medaly Claudia (2025)
The granting of precautionary measures prior to the beginning of an arbitration, is essential to achieve the effectiveness of the future arbitral award. The current arbitration legislation allows judicial collaboration in this matter by regulating the opportunity for its dictation, as well as the grounds for its extinction. The termination of precautionary measures is closely related to the disappearance of the requirements for their concession, such as verisimilitude in law, danger in delay and adequacy. However, our legal system allows that a precautionary measure may be extinguished in case the arbitral tribunal is not constituted within a maximum period of 90 business days from its execution. In this sense, the purpose of this thesis is to analyze the reasonableness of this case of termination with a view to protecting the right to effective judicial protection. To this end, the various situations that may occur prior to the constitution of the arbitral tribunal will be studied in order to demonstrate that the delay in the constitution of the arbitral tribunal may be due to situations beyond the control of the measure´s beneficiary. After that, an appropriate distribution of the risk due to the delay in the progress of the arbitral proceedings that prevent the constitution of the arbitral tribunal, will be proposed, as well as a proposal for the amendment of article 47 of the Arbitration Law containing an intermediate solution that seeks to protect the precautionary tutelage, but at the same time to prevent an abusive exercise of it.